Correlación diagnóstica pre y posoperatoria en la desproporción cefalo - pélvica en ginecología y obstetricia del hospital Isidro Ayora de Loja periodo junio - noviembre 2012. - Samaniego Rojas, Andres Felipe (2013)
The present study aimed to establish the diagnostic correlation pre-and post -operative cephalopelvic disproportion in the area of Gynecology and Obstetrics Hospital "Isidro Ayora" of Loja in the period June to November 2012. It is a descriptive study, transversal, we applied a data collection sheet and inclusion and exclusion criteria to determine the degree of correlation between the initial measurement and subsequent diagnosis to cesarean section. The sample included 50 full term pregnant patients admitted to the Obstetrics and Gynecology Hospital "Isidro Ayora" Loja diagnosed with cephalopelvic disproportion. Of which 88 % are correlated with previous diagnosis, while the remaining 12% has no relation to their initial diagnosis. Regarding the application of the standards set by the Ministry of Public Health to dystocia type Fetus - pelvic disproportion Pelvic narrowness found that, 88 % meet proposed regulations, while remaining 12% not base his diagnosis on such standards or not record the assessment on relevant gynecological history. KEYWORDS: Dystocias, Cephalopelvic Disproportion, Correlation, Caesarea, Pelvic Stricture.